Impact of the complementary electronic nature of C–X and M–X halogens and intramolecular X⋯O interaction on supramolecular assemblies of Zn(ii) complexes of o-halophenyl substituted hydrazides. Issue 12 (2nd March 2017) - Mandal, Arkalekha; Patel, Bhisma K.; Shukla, Rahul; Chopra, Deepak
Abstract : The importance of halogen bonding in locking the molecular conformation is rationalised in zinc complexes of halogen containing hydrazides. Abstract : The disparity in the electronic nature of organic (C–X) and inorganic (M–X) halogens in a supramolecular context has been demonstrated herein. Metal complexes [Zn(hyd-X )Cl2 ]· n DMF of three o -halophenyl substituted hydrazide based ligandshyd-X (hyd = hydrazide, X = F, Cl and Br) have been synthesized and characterized by single crystal XRD. The C–X halogen atom in these complexes is involved in either intramolecular X⋯O interaction (when X = Cl/Br) or intramolecular N–H⋯X (when X = F) hydrogen bonding. Supramolecular networks propagated via intermolecular C–X⋯N halogen bonds and N–H⋯X(M) hydrogen bonds are observed in crystal structures of the complexes. Intramolecular X⋯O interaction and intramolecular N–H⋯F hydrogen bonds exert decisive roles in locking the molecular conformation of these compounds. DFT, AIM and NBO studies have been employed to acquire quantitative accounts of the halogen mediated non-covalent interactions.